Retinoic acid regulates immune responses by promoting IL-22 and modulating S100 proteins in viral hepatitis - Jie, Zuliang (J Immunol, 2017)
Although large amounts of vitamin A and its metabolite all-trans retinoic acid (RA) are stored in the liver, how RA regulates liver immune responses during viral infection remains unclear. In this study, we demonstrated that IL-22, mainly produced by hepatic γδ T cells, attenuated liver injury in adenovirus-infected mice. RA can promote γδ T cells to produce mTORC1-dependent IL-22 in the liver, but inhibits IFN-γ and IL-17. RA also affected the aptitude of T cell responses by modulating dendritic cell (DC) migration and co-stimulatory molecule expression. These results suggested that RA plays an immunomodulatory role in viral infection. Proteomics data revealed that RA down-regulated S100 family protein expression in DCs, as well as NF-κB/ERK pathway activation in these cells. Furthermore, adoptive transfer of S100A4-repressed, virus-pulsed DCs into the hind foot of naïve mice failed to prime T cell responses in draining lymph nodes. Our study has demonstrated a crucial role for RA in promoting IL-22 production and tempering DC function through down-regulating S100 family proteins during viral hepatitis.